Differentiation of acute versus chronic skin rejection in a rodent model of vascularized composite allotransplantation - Thomé, Julia; Lind, Maike; Schmitt, Maxime; Schneider, Laura; Kiefer, Jurij; Schäfer, Rebecca; Freise, Emma; Christmann, Thierry; Kreuzaler, Sheena; Kollár, Branislav; Eisenhardt, Steffen U. (Frontiers in Immunology, 2025)
BackgroundVascularized composite allografts (VCA) have evolved to be a potential option in complex reconstructive surgery. However, managing acute and chronic allograft rejection remains challenging. This study underlines differences between acute and chronic rejection in skin based on Banff criteria using rodent VCA models, enhancing comprehension of the underlying immunopathology.MethodsWe compared whole tissue sections of fresh frozen skin from a rat hindlimb allograft transplantation model of acute and chronic rejection, respectively (n=7), stained with Hematoxylin Eosin-, Periodic Acid Schiff- and Masson’s Trichrome. Assessment followed the Banff 2007 working classification of skin-containing composite tissue allograft pathology, also considering the Banff 2022 VCA Working Group’s consensus. Immune cell infiltration was further analyzed via immunofluorescence.ResultsHistopathological criteria effectively distinguished both acute and chronic rejection from healthy control skin. However, substantial overlap was observed, including perivascular infiltrates. Chronic rejection presented distinct features such as band-like lymphohistiocytic infiltrates, loss of rete ridges and adnexal structures, fibrosis, vasculitis, and allograft vasculopathy. Immune cell infiltration increased in both rejection groups.ConclusionThis study validates the application of the updated Banff classification in rat VCA rejection models, highlighting overlapping and distinct features of acute and chronic rejection patterns. Clear differentiation between acute and chronic rejection remains challenging, as no single criterion provides absolute diagnostic certainty and multiple pathways with transitional forms are involved. In our cohort, allograft vasculopathy, loss of rete ridges, and band-like lymphohistiocytic infiltrates were the most distinctive features, underscoring the need for an integrative diagnostic approach. The findings reflect patterns seen in human chronic active rejection and underscore the need for further research to better understand the mechanisms driving sustained inflammation and tissue remodeling in VCA rejection.